Physical activity behavior in the first month after mild traumatic brain injury is associated with physiological and psychological risk factors for chronic pain. (29th November 2021) - Naugle, Kelly M.; Corrona, Sam; Smith, Jared A.; Nguyen, Tyler; Saxe, Jonathan; White, Fletcher A.
Abstract : Lower levels of physical activity in the first month after mild TBI predicts decreased conditioned pain modulation and greater pain catastrophizing in patients with mild TBI. Abstract: Objective: The purpose of this study was to determine whether self-reported physical activity (PA) in the first month after mild traumatic brain injury (mTBI) predicts endogenous pain modulatory function and pain catastrophizing at 1 to 2 weeks and 1 month after injury in patients with mTBI. Methods: Patients with mild traumatic brain injury completed study sessions at 1 to 2 weeks and 1 month after injury. Assessments included a headache survey, Pain Catastrophizing Scale, International Physical Activity Questionnaire-Short Form, and several quantitative sensory tests to measure endogenous pain modulatory function including conditioned pain modulation (CPM), temporal summation, and pressure pain thresholds of the head. Hierarchical linear regressions determined the relationship between the PA variables (predictors) and pain catastrophizing and pain modulation variables (dependent variables) cross-sectionally and longitudinally, while controlling for potential covariates. Results: In separate hierarchical regression models, moderate PA, walking, and total PA at 1 to 2 weeks after injury predicted pain inhibition on the CPM test at 1 month, after controlling for significant covariates. In addition, a separate regression revealed that minutes sitting at 1 month predicted CPM at 1 month. Regarding predicting pain catastrophizing, the regression results showed that sitting at 1 to 2 weeks after injury significantly predicted pain catastrophizing at 1 month after injury. Conclusion: Greater self-reported PA, especially moderate PA, 1 to 2 weeks after injury longitudinally predicted greater pain inhibitory capacity on the CPM test at 1 month after injury in patients with mTBI. In addition, greater sedentary behavior was associated with worse pain inhibition on the CPM test and greater pain catastrophizing at 1 month after injury.